Capability hierarchy in electronic procurement and procurement process performance: An empirical analysis. Issue 6 (7th August 2013) - Mishra, Abhay Nath; Devaraj, Sarv; Vaidyanathan, Ganesh
Abstract: This paper examines the interrelationship between two hierarchically structured functional capabilities pertinent in the organizational procurement process, and the impact of these capabilities on procurement process performance. These functional capabilities operate at different levels in an organization's procurement process. We draw upon resource‐ and knowledge‐based views of the firm to theorize that in this hierarchy of information technology‐enabled procurement capabilities, the higher‐level capability – procurement integration competence – enables firms to develop and deploy a lower‐level capability – digital procurement competence. Further, we theorize that the lower‐level capability impacts procurement process performance directly and completely mediates the relationship between higher‐level capability and performance. Thus, although performance is impacted directly only by the lower‐level capability, the higher‐level capability facilitates the development and use of the lower‐level capability. Our research model is tested using survey data from a large sample of 412 manufacturing firms. The results provide strong support for the proposed research model. In particular, we find that as hypothesized, the impact of procurement integration competence on performance is completely mediated by digital procurement competence. Our results suggest that when examined at the procurement process level, the impact of higher‐level capabilities may be manifested completely through the lower‐level capabilities. Theoretical and practical implications of the research are discussed.